A New Highly Anisotropic Rh-Based Heusler Compound for Magnetic Recording - Coey, John; Stamenov, Plamen (My University, 2020)
The development of high-density magnetic recording media is limited by superparamagnetism in very small ferromagnetic crystals. Hard magnetic materials with strong perpendicular anisotropy offer stability and high recording density. To overcome the difficulty of writing media with a large coercivity, heat-assisted magnetic recording was developed, rapidly heating the media to the Curie temperature Tc before writing, followed by rapid cooling. Requirements are a suitable Tc, coupled with anisotropic thermal conductivity and hard magnetic properties. Here, Rh2CoSb is introduced as a new hard magnet with potential for thin-film magnetic recording. A magnetocrystalline anisotropy of 3.6 MJ m−3 is combined with a saturation magnetization of μ0Ms = 0.52 T at 2 K (2.2 MJ m−3 and 0.44 T at room temperature). The magnetic hardness parameter of 3.7 at room temperature is the highest observed for any rare-earth-free hard magnet. The anisotropy is related to an unquenched orbital moment of 0.42 μB on Co, which is hybridized with neighboring Rh atoms with a large spin–orbit interaction. Moreover, the pronounced temperature dependence of the anisotropy that follows from its Tc of 450 K, together with a thermal conductivity of 20 W m−1 K−1, make Rh2CoSb a candidate for the development of heat-assisted writing with a recording density in excess of 10 Tb in.−2.
PUBLISHED
cited By 0
Keywords: 4d magnetism; Magnetic hardness parameter; Magnetic recording; Magnetocrystalline anisotropy; Tetragonal Heusler alloys